Reference and its role in textual cohesion (The Two Holy Mosques’ sermons in the 2020 Corona crisis as an example) - Al-Hamrani, Amina Muhammad; Bassiouni, Hoda Eid (Journal of Arabic Language Sciences and Literature, 2024)
This study aimed to reveal how the meanings and values called for in the sermons of the Two Holy Mosques were highlighted in light of the Corona crisis from the perspective of textual linguistics, and to show an aspect of textual cohesion at its various levels, and to identify the features of textual cohesion through references of all kinds, and accordingly, The following problem was raised: How did the referral contribute to the consistency of the Two Holy Mosques’ sermons during the Corona crisis? The importance of this research lies in clarifying the role of referral in the coherence and cohesion of the text and removing ambiguity and confusion from the referring expressions, by attributing these expressions to their references so that the recipient can understand the text. The researcher followed the descriptive approach, and the study reached several results, including: The referral with pronouns It was the most common in the sample, including internal referral, and most of it came in the form known in the language, which is tribal referral.
Keywords: Textual cohesion; referral; the sermons of the Two Holy Mosques in the 2020 Corona crisis